Ageing remarkably alters the toxicity of carbon black particles towards susceptible cells: determined by differential changes of surface oxygen groups. Issue 6 (21st May 2020) - Wei, Shuting; Qi, Yu; Ma, Li; Liu, Yongchun; Li, Guangke; Sang, Nan; Liu, Sijin; Liu, Yajun
Abstract : Ageing process remarkably alters the toxicity of carbon black particles towards susceptible cells via changing the species of their surface oxygen groups. Abstract : We uncover that O3 -induced ageing dynamically alters the surface O-functionalities of carbon black (CB) nanoparticles, a model of airborne particles. The consequent distinct bioreactivity and toxicity towards susceptible cells under low-dose exposure are largely attributed to the variant species of O-functionalities, thereby signifying the importance of the environmental ageing process in changing CB toxicity features.